Analyzing Nexus between financial reforms and savings in Pakistan: an econometric investigation - Awais, Muhammad; Kausar Kiani, Adiqa; Mohd Thas Thaker, Mohamed Asmy; Raza, Asif; Qaim, Sarah (Primrose Hall Publishing Group, 2021)
Development economists and policy makers across the globe extensively discuss the factors affecting the growth performance of developing economies. The recent financial crisis and poor performance of financial sector instigated the economies to shift from suppressive regulations to deregulations of interest rate along with implementation of a few other open options. International funding agencies provided technical as well as financial assistance to carry on the agenda and achieve optimal policy mix. Keeping in view its importance, present study tests the empirical nexus between financial reforms and savings in Pakistan. Data set ranges from 1980 to 2015 and application of econometric method of Johansen co integration method found the short run and long run saving function. Major findings suggested that financial reforms gave a boost to saving rate and hence contributed towards overall performance enhancement in Pakistan. The results of other control variables show positive and robust relationship according to theoretical background.